Cloning, Expression, and Catabolite Repression of a Gene Encoding β-Galactosidase of Bacillus megaterium ATCC 14581 - Shaw, Gwo-Chyuan (American Society for Microbiology, 1998)
A gene encoding β-galactosidase, designated mbgA, was isolated from Bacillus megaterium ATCC 14581. Chromosomal β-galactosidase production could be dramatically induced by lactose but not by isopropyl-β-d-thiogalactopyranoside (IPTG) and was subject to catabolite repression by glucose. Disruption of mbgA in the B. megaterium chromosome resulted in loss of lactose-inducible β-galactosidase production. A 27-bp inverted repeat was found to overlap the mbgA promoter sequence. Two partially overlapping catabolite-responsive elements (CREs) were identified within the inverted repeat. Base substitutions within CRE-I and/or CRE-II caused partial relief from catabolite repression. The results suggest that the 27-bp inverted repeat may serve as a target for a catabolite repressor(s).